Laboratory Parameter Profile in Hepatocellular Carcinoma Patients admitted to the wards of Internal Medicine at an Indonesian Tertiary Hospital - Namira Amelia Septiarini; Puspa Wardhani; Yulia Nadar Indrasari; Ummi Maimunah (Current Internal Medicine Research and Practice Surabaya Journal, 2026)
Background: Hepatocellular Carcinoma (HCC) is a liver cancer caused by abnormal cell changes, potentially fatal, and is the eighth most common cancer in the world. Diagnosis can be done through liver function tests, tumor markers, and imaging examinations. Thus study aimed to determine the profile of laboratory parameters in HCC patients at Dr. Soetomo Hospital Surabaya in 2020-2022. Methods: The method used was a retrospective study of 67 patient medical records with secondary data collection through total sampling techniques. Laboratory tests performed included SGOT, SGPT, Albumin, Direct Bilirubin, Total Bilirubin, PT, aPTT, and AFP. Results: This study showed that the most common age group was 55-59 years, with the majority of patients being male (70.14%) from East Java (91%). The main complaints were abdominal discomfort and abdominal enlargement (61.19%), with the highest causative factor being Hepatitis B (44.77%). Most patients were at BCLC stage D (17.18%). Laboratory parameters showed median and minimum maximum values for SGOT were 135 (20.76–1436), SGPT 59 (17–671), albumin level 2.96 ± 0.62, direct bilirubin 1 (0.02–22.96), total bilirubin 2.05 (0.09–30.84), PT 14.7 (10.1–47.7), and aPTT 30.2 (20.7–85.5). A total of 16 patients had AFP levels above 400ng/mL. The results of USG and CT Scan examinations showed multiple tumors in most patients. Conclusion: The profile of HCC patients in the inpatient room internal medicine Dr. Soetomo Hospital Surabaya in 2020-2022 was dominated by male patients aged 55-59 years, the main complaint was abdominal discomfort, the most common risk factors were Hepatitis B, BCLC stage D, abnormal liver function, total AFP levels above 400 ng/mL, and USG and CT-Scan examinations showed multiple tumors.